Antecedents of zakat payers trust in an emerging zakat sector: The role of board capital and organisational behaviour. - Mustafa, M. O. A.; Muslim, H. S. M.; Adnan, Muhammad Akhyar (IIUM Press, 2011)
The main objective behind establishment of effective govemance in organizations is to ensure mutual trust among the stakeholders. Incidentally, viliually all studies on organizational trust have not investigated the role of governance in trust building. In the research reported in this paper, the role of govemance in the model of zakat trust which was developed and validated based on responses from Nigerian zakat payers was shown. Such knowledge will help zakat managers to influence zakat payers' trust and patronage. In the study, we explore antecedents of trust; develop measurement scales used to explore the relationship between trust and the factors. Four factors, board capital, disclosure practices, nature of zakat institutions, and stakeholder management were identified through the use of structural equation modeling as being antecedents of trust. Since this is the first study ofzakat payers trust, it constitutes a significant contribution to knowledge and practice.The implications for zakat institutions in building trust of zakat payers are discussed. The zakat payer-trust model represents the main contribution of this study.